Integrating task-based and blended learning to improve sight reading and instrumental performance - Fu, Yalu; Kanjanakate, Supawadee; Jantharajit, Nirat (Asian Journal of Contemporary Education, 2025)
The present study aims to explore the efficacy of an instructional method combining Task-Based Learning (TBL) and Blended Learning (BL) for developing sight-reading skills and musical instrument playing among undergraduate students of Chinese traditional instrumental music. A quasi-experimental design was employed with 50 second-year students from the Sichuan Conservatory of Music, who were allocated to experimental and control groups. The experimental group received a six-phase instructional intervention with TBL activities and blended materials in 20 sessions. Post-test findings revealed the experimental group's significant improvement in both sight-reading ability and musical instrument playing, with medium to large effect sizes. The approach successfully supported technical skill acquisition, artistic expression, and self-regulated learning. The synthesis of TBL and BL has been shown to be a highly effective pedagogical approach to enhancing the technical and expressive dimensions of musical education. The six-stage model exhibited high instructional coherence and flexibility, providing valuable guidelines for curricular change in performance-oriented music education.